Pengembangan Alat Peraga dan Modul Listrik Magnet Untuk Pembelajaran IPA Fisika Di SMP - Mitra Rahayu; Evy Nurvitasari; Jeffri Parrangan (Faculty of Teacher Training and Education, Musamus University, 2020)
Research has been conducted which aims to increase understanding of the concept of material Electric Magnets through practicum methods using the Magnetic Electric Trainer which is created and developed using tools and materials in Merauke. Product development is done by making Magnetic Electric teaching aids for electromagnetic material, Induction GGL, Induction on straight wire and electric motors. Where props are made using tools and simple materials that are easily obtained, such as plywood, plastic pipes, cables and magnets. From the results of the application of the use of the Magnetic Electric teaching aids in SMP N 13 Merauke in class VIIID students, with the KKM value of 70 Natural Sciences lessons, the pretest results showed that no student passed the KKM. Then for the quiz score obtained by 5 students who passed the KKM and for the post-test scores obtained 18 students who passed the KKM with a total of grade VIII D students were 23 people consisting of 15 men and 8 women. Besides the Electric Magnet teaching aids, the Magnet Magnet practicum module was also developed. Before testing the teaching aids and the Electric Magnet module it is validated by experts.